2013
DOI: 10.1038/nchembio.1158
|View full text |Cite
|
Sign up to set email alerts
|

Essential nontranslational functions of tRNA synthetases

Abstract: Nontranslational functions of vertebrate aminoacyl tRNA synthetases (aaRSs), which catalyze the production of aminoacyl-tRNAs for protein synthesis, have recently been discovered. While these new functions were thought to be ‘moonlighting activities’, many are as critical for cellular homeostasis as the activity in translation. New roles have been associated with cytoplasmic forms as well as with nuclear and secreted extracellular forms that impact pathways for cardiovascular development, the immune response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
322
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(329 citation statements)
references
References 100 publications
3
322
0
4
Order By: Relevance
“…The two TrpRS bind tRNAs with different anticodons. WARS2 binds mitochondrial tRNA Trp with the anticodon UCA, which codes for Trp in the mitochondria of humans 40 , while WARS binds cytoplasmic tRNA Trp, which contains the standard anticodon CCA. Little is known about free Trp concentrations in mitochondria and it is therefore not clear how mitochondrial Trp concentrations are affected by Trp depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The two TrpRS bind tRNAs with different anticodons. WARS2 binds mitochondrial tRNA Trp with the anticodon UCA, which codes for Trp in the mitochondria of humans 40 , while WARS binds cytoplasmic tRNA Trp, which contains the standard anticodon CCA. Little is known about free Trp concentrations in mitochondria and it is therefore not clear how mitochondrial Trp concentrations are affected by Trp depletion.…”
Section: Discussionmentioning
confidence: 99%
“…These domain additions are not needed for catalysis, but rather to endow the synthetases with functions beyond translation. These functions are associated with secreted, extracellular forms and with nuclear forms that are active in many different cell-signaling pathways (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In addition, a recent study demonstrated that a novel domain, appended to SerRS at the time of the invertebrate to vertebrate transition, was essential for development of the closed vascular system (13).…”
mentioning
confidence: 99%
“…In addition, a recent study demonstrated that a novel domain, appended to SerRS at the time of the invertebrate to vertebrate transition, was essential for development of the closed vascular system (13). Thus, novel domains added to tRNA synthetase are endowed with nontranslation functions that are as essential as the activity of the synthetase in protein synthesis (12).…”
mentioning
confidence: 99%
“…5, Após ser sintetizada, a proteína precisa ser dobrada para atingir sua conformação ativa (adaptado de Lehninger (2006). Na etapa de ativação de AA, que ocorre no citosol, cada um dos 20 AA é covalentemente ligado a um tRNA específico às custas de ATP e enzimas ativadoras dependentes de Mg +2 (aminoacil-tRNA-sintases), tornando o tRNA "carregado" (Monajjemi et al, 2014) sendo, em seguida, transferido para a extremidade 3' do tRNA cognato (Guo & Schimmel, 2013).…”
Section: Mecanismos Envolvidos Na Síntese Proteicaunclassified